2000
DOI: 10.1128/jb.182.10.2900-2908.2000
|View full text |Cite
|
Sign up to set email alerts
|

Gene Rearrangements in the vsa Locus of Mycoplasma pulmonis

Abstract: The vsa genes of Mycoplasma pulmonis encode the V-1 lipoproteins. Most V-1 proteins contain repetitive domains and are thought to be involved in mycoplasma-host cell interactions. Previously, we have reported the isolation and characterization of six vsa genes comprising a 10-kb region of the genome of M. pulmonis strain KD735-15. In the current study, vsa-specific probes were used to clone several fragments from a genomic library of KD735-15 DNA and assemble a single 20-kb contig containing 11 vsa genes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
90
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 39 publications
0
90
0
Order By: Relevance
“…Variable proteins are often subjected to both size and phase variation, and many are members of multigene families. The proteins of a multigene family are often differentially expressed, and chromosomal rearrangements occur to allow transcription of one gene instead of another (Lysnyansky et al, 1999;Citti et al, 2000;Markham et al, 1994Markham et al, , 1999 FlitmanTene et al, 2000; Glew et al, 2000; Roske et al, 2001;Shen et al, 2000;Horino et al, 2003;Noormohammadi et al, 1998).…”
Section: -7247 G 2004 Sgm Printed In Great Britain 4009mentioning
confidence: 99%
See 1 more Smart Citation
“…Variable proteins are often subjected to both size and phase variation, and many are members of multigene families. The proteins of a multigene family are often differentially expressed, and chromosomal rearrangements occur to allow transcription of one gene instead of another (Lysnyansky et al, 1999;Citti et al, 2000;Markham et al, 1994Markham et al, , 1999 FlitmanTene et al, 2000; Glew et al, 2000; Roske et al, 2001;Shen et al, 2000;Horino et al, 2003;Noormohammadi et al, 1998).…”
Section: -7247 G 2004 Sgm Printed In Great Britain 4009mentioning
confidence: 99%
“…Variable proteins are often subjected to both size and phase variation, and many are members of multigene families. The proteins of a multigene family are often differentially expressed, and chromosomal rearrangements occur to allow transcription of one gene instead of another (Lysnyansky et al, 1999;Citti et al, 2000;Markham et al, 1994Markham et al, , 1999 FlitmanTene et al, 2000; Glew et al, 2000; Roske et al, 2001;Shen et al, 2000;Horino et al, 2003;Noormohammadi et al, 1998).Mmymy SC was originally thought not to exhibit intraclonal variability, but a variable surface protein Vmm (Persson et al, 2002) that undergoes reversible phase variation has recently been identified. The vmm gene has been demonstrated in all Mmymy SC strains as a single copy and is regulated at the transcriptional level by dinucleotide (AT) insertions or deletions in a repetitive region of the promoter spacer.…”
mentioning
confidence: 99%
“…For example, M. pulmonis has the vsa proteins and M. pneumoniae has the P1 protein present many times each in the genome (Himmelreich et al 1996;Chambaud et al 2001). In the case of M. pulmonis, a promoter sequence is moved from copy to copy of vsa to effect antigenic switching (Bhugra et al 1995;Shen et al 2000). In M. pneumoniae, it is believed that homologous recombination transfers different variants of the P1 gene into an actively transcribed locus (Kenri et al 1999).…”
Section: Putative Major Surface Antigenmentioning
confidence: 99%
“…DNA rearrangements associated with changes in gene expression have also been found for Vsps (20,22). Two other well-described systems involving DNA rearrangements in mycoplasmas are the vsa and hsd systems in M. pulmonis (5,35,37,38). Both systems generate variation in expression of a given product by exchanging the C-terminal region of the active gene with the open reading frame (ORF)…”
mentioning
confidence: 99%